Pengaruh Berbagai Konsentrasi Air Rebusan Ketumbar (Coriandrum Sativum) terhadap Penurunan Angka Kuman Tiang Infus di Puskesmas Rawat Inap Sewon I Bantul - Dwi Purwanti; Sri Muryani; Choirul Amri (Poltekkes Kemenkes Yogyakarta, 2018)
Infection prevention and control is an effort to prevent and minimize the occurrence of infection inpatients, officers, and community around health care facilities; through cleaning and disinfection of bed surface, bedside equipments and the often-touched bed edges. A preliminary study conducted in Puskesmas Sewon 1 of Bantul found that one intravenous pole had micobrial number of 208,67 colony/cm2 and had never disinfected. Nonetheless, chemical disinfectants usually leave residues. The safer with no-residue disinfectant is the vegetable-based ones, and one of the example is coriander. This research was a true experiment with pre-test post-test with control group design. The disinfectant used was coriander stew water with three various concentrations, i.e. 10 %, 20 % and 30 %, which were applied to eight intravenous poles. The data were analysed by one way anova test at 5 % level of significance. Descriptively, the average decrease ofbacteria number from 10 % concentration was 43,15 colony/cm2 (69,7%), from 20 % concentration was 65,87 colony/cm2 (40,3 %), from 30 % concentration was 50 colonies/cm2 (46,1 %), and from the control group was 38,94 colonies/cm2 (61,69 %). However, the p-value yielded from the statistical analysis was 0,525 which means that those bacteria number reduction of intravenous pole from the various concentration of coriander stew water disinfectant are not significantly differrent.